2021
DOI: 10.1111/tri.13814
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐specific waitlist outcomes in liver transplantation – a retrospective study

Abstract: Summary This study aimed to evaluate possible discrepancies in waitlist outcomes between liver diseases, including alcohol‐related liver disease (ALD), nonalcoholic steatohepatitis (NASH), hepatitis C virus infection (HCV), primary biliary cirrhosis (PBC), and primary sclerosing cholangitis (PSC). Patients registered for liver transplantation from January 11, 2016, to June 30, 2018, were evaluated using OPTN/UNOS registry. Waitlist outcomes were compared between the five‐disease groups. Patients were categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…It was reported that disease progression and LT waitlist outcomes might differ between the primary etiologies. [ 21 ] The NN models was created by including primary liver disease etiologies which showed excellent AUC‐ROC and AUC‐PR in the major disease etiology groups (Table S5). Because the NN model considers patients' primary liver disease, allocation system using NN can consider the difference in disease progression according to the liver disease etiologies and provide more accurate prediction of mortality according to the liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that disease progression and LT waitlist outcomes might differ between the primary etiologies. [ 21 ] The NN models was created by including primary liver disease etiologies which showed excellent AUC‐ROC and AUC‐PR in the major disease etiology groups (Table S5). Because the NN model considers patients' primary liver disease, allocation system using NN can consider the difference in disease progression according to the liver disease etiologies and provide more accurate prediction of mortality according to the liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis on patients from OPTN/UNOS registry showed that, in comparison to patients with alcoholic liver disease, the risk of 90-day and 1-year waitlist mortality was significantly higher in NASH patients (p=0.042 and p=0.008) (45). MELD-Na score, CKD stage >3 and hyponatremia were significantly associated to mortality.…”
Section: Waiting-list Managementmentioning
confidence: 99%
“…A recent analysis on patients from OPTN (Organ Procurement and Transplantation Network)/UNOS (United Network for Organ Sharing) registry showed that, in comparison to patients with alcoholic liver disease (ALD), the risk of 90-day and 1-year waitlist mortality was significantly higher in NASH patients ( P =0.042 and P =0.008) [ 45 ]. Model for End-Stage Liver Disease-Na (MELD-Na) score, Chronic Kidney Disease (CKD) stage >3 and hyponatremia were significantly associated to mortality.…”
Section: Waiting-list Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the prognostic utility of the MELD‐Na score is increasingly recognized as being less reliable in ALD patients with high MELD scores that actually have a mortality rate comparable to non‐ALD patients with lower MELD scores. ( 11 ) With that in mind, several groups have suggested that a minimum duration of abstinence for patients with ALD and particularly concomitant acute kidney injury may be reasonable to facilitate hepatic recovery and avoid unnecessary transplants. However, this does not imply that patients with ALD are less deserving of LT.…”
Section: Figmentioning
confidence: 99%